Cellular automata and discrete complex systems : 20th International Workshop, AUTOMATA 2014, Himeji, Japan, July 7-9, 2014, Revised Selected Papers - Isokawa, Teijiro; Imai, Katsunobu; Matsui, Nobuyuki; Peper, Ferdinand; Umeo, Hiroshi (Lecture Notes in Computer Science, 2015)
This book constitutes revised selected papers from the 20th International Workshop on Cellular Automata and Discrete Complex Systems, AUTOMATA 2014, held in Himeji, Japan, in July 2014. The 10 regular papers included in this volume were carefully reviewed and selected from a total of 25 submissions. It also contains one invited talk in full paper length.